Impact of maternal risk factors on the structure and function of the heart in newborns. (3rd October 2022) - Noerregaard, M; Voegg, R O B; Raja, A A; Sillesen, A S; Joergensen, F S; Basit, S; Boyd, H; Iversen, K K; Bundgaard, H
Abstract: Introduction: Maternal factors such as smoking during pregnancy, advanced age, and obesity are associated with increased risk of complex congenital heart defects in the offspring. It is unknown whether maternal risk factors may also cause subtle abnormalities in cardiac structure and function. Purpose: To investigate whether the following maternal factors: advanced age, high body mass index (BMI), and smoking during pregnancy are associated with changes in left ventricle (LV) dimensions and systolic function in the newborn child. Methods: Data was obtained as part of a population-based cohort study with prenatal inclusion and postnatal transthoracic echocardiography (TTE) of newborns within 60 days of birth. The TTE protocol included measurements of: Interventricular septal thickness at end-diastole (IVSd), LV posterior wall thickness at end-diastole (LVPWd), LV internal diameter at end-diastole (LVIDd) and LV internal diameter at end-systole (LVIDs). Fractional shortening (FS) was calculated by use of Teicholz's formula. Children of mothers with data available on age, BMI, and smoking status, respectively, were divided into the following groups depending on whether their mothers were: of young age <25 years, 25–29 years, 30–34 years (reference group), 35–39 years, and advanced age ≥40 years; underweight BMI <18.5, normal range BMI 18.5–24.9 (reference group), preobese BMI 25–29.9, and obese BMI ≥30; smoking or nonsmoking (reference group). Associations between different groups with each maternal risk factor and newborn LV parameters were analysed using a multiple linear regression model. Results: Children of mothers with advanced age at the time of childbirth (n=1, 411) had significantly smaller LVIDd and LVIDs (Table 1) compared to children of mothers in their early thirties (n=10, 045). Children of preobese (n=4, 707) and obese mothers (n=2, 138) had significantly smaller LVIDd and LVIDs than children of mothers in the normal BMI range (n=17, 654). Children of mothers who smoked during pregnancy (n=808) had significantly larger LVPWd than children of non-smoking mothers (n=24, 072). A significant difference in FS was only seen in children of obese mothers. Subanalyses of the quantity of maternal smoking (available data in n=548 [67.8%] of mothers who smoked during pregnancy) showed that children of heavy smoking mothers (≥15 cigarettes/day, n=101), had significantly thicker IVSd and LVPWd compared with children of nonsmoking mothers, whereas no significant effect was identified in newborns of mothers smoking less than 15 cigarettes per day (Table 2). Conclusions: Systematic population-based echocardiography of newborns showed that an increased maternal BMI and maternal age above 40 years were associated with smaller LV cavity dimensions in the offspring and that heavy smoking during pregnancy was associated with increased LV myocardial thickness. FS was only affected in children of obese mothers. The long-term effects of these novel findings are unknown. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Herlev-Gentofte Hospital Internal Funding for Cardiological Research andThe Novo Nordisk Foundation